Seasonal variation in density dependence in age‐specific survival of a long‐distance migrant. Issue 10 (1st October 2013) - Lok, Tamar; Overdijk, Otto; Tinbergen, Joost M.; Piersma, Theunis
Abstract : Density dependence in vital rates is key to population regulation. Rather than being constant, the strength of density dependence may vary throughout the year, but empirical evidence is limited. Based on 22 years of data of color‐banded birds from a recovering population of Eurasian Spoonbills Platalea leucorodia leucorodia, we show, for the first time, seasonal variation in density dependence in survival of a long‐distance migrating bird. Combining resightings and dead recoveries at breeding, stopover, and nonbreeding areas enabled us to (1) separate true survival from permanent emigration from the breeding area, and (2) estimate survival in three seasons: summer, early winter (including autumn migration), and late winter (including spring migration). Accompanying the rapid population growth, juvenile annual survival initially increased, manifested in early winter, but thereafter, at high population sizes, it strongly decreased through a combination of decreasing survival in all seasons. Annual survival of subadult (second‐ and third‐year) and adult birds decreased more gradually with increasing population size, with density dependence occurring in early winter for subadults and late winter for adults. Thus, the shape and strength of density dependence in survival varied with age and season. Understanding the seasonal timing of density dependence, especially with reference to underlying mechanisms, is important for the design of effective conservation strategies.